The view of doctors and the use of medicinal plants by the health system (Research, Society and Development, 2022)
Medicinal plants have been part of the history of humanity since its beginnings, being indispensable in the health of civilizations. The use of medicinal plants and herbal medicines is a widespread practice around the world and encouraged by the World Health Organization (WHO), especially in developing countries, as it may be the only therapeutic resource for some communities and ethnic groups. However, its use must be done consciously, requiring professionals with skills regarding the adequate prescription of this therapy, as is the case of physicians. With this in mind, the study aims to understand, through literature, the view of doctors about medicinal plants through the health system. The methodology used in the research denotes a narrative review of the literature, carried out from databases such as the Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Library Virtual Health (BVS) and other reliable databases. The guiding question of the research is: What is the view of doctors regarding the use of medicinal plants by the health system? The search strategy used was the combination of Health Sciences Descriptors (DeCS): Physicians. Medicinal plants. Health system. The literature review initially addressed the characterization of medicinal plants, then the use of herbal medicines in primary care and finally, the view of doctors regarding the use of medicinal plants. Thus, it is concluded that doctors have insufficient knowledge about the prescription and use of medicinal plants, since the academic contents do not satisfactorily cover the teaching of Phytotherapy. It was also noted that the literature is still scarce and does not cover the reality as recommended by the Ministry of Health.